Heart the lover : a novel [large type] - King, Lily (Thorndike Press, a part of Gale, a Cengage Company, 2025)
"Our narrator understands good love stories--their secrets and subtext, their highs and their free falls. But her greatest love story, the one she lived, never followed the simple rules. In the fall of her senior year of college, she meets two star students from her 17th-Century Lit class: Sam and Yash. Best friends living off-campus in the elegant house of a professor on sabbatical, the boys invite her into their intoxicating world of academic fervor, rapid-fire banter and raucous card games. They nickname her Jordan, and she quickly discovers the pleasures of friendship, love and her own intellectual ambition. Youthful passion is unpredictable though, and she soon finds herself at the center of a charged and intricate triangle. As graduation comes and goes, choices made will alter these three lives forever. Decades later, Jordan is living the life she dreamed of, and the vulnerable days of her youth seem comfortably behind her. But when a surprise visit and unexpected news bring the past crashing into the present, Jordan returns to a world she left behind and is forced to confront the decisions and deceptions of her younger self."--